THE INFLUENCE OF THE BRITISH STYLE DEBATE LEARNING MODEL BASED ON LOGICAL INFERENCE IN ENHANCING STUDENTS' SCIENTIFIC THINKING ABILITIES - Maghribi, Andre Nurul; Aristiawan, Aristiawan (Science Education, Institut Agama Islam Negeri Ponorogo, 2023)
Science education should be able to help students acquire scientific thinking skills. However, the reality in the field shows that the average value of students' scientific thinking is only 65.35%, which is classified as moderate. to overcome this problem, the implementation of the English Style Debate Learning model based on logical reasoning was introduced to students. The purpose of this study is to determine the impact of the implementation of this model on students at SMPN 1 Sambit, Ponorogo. the research method used is quantitative with experimental type. The research design used was quasi-experimental design. the sampling technique used was cluster random sampling. The one-tailed t-test results showed that students' scientific thinking skills when using the logical inference-based English Style Debate Learning model were superior to their skills when using the Generative Learning model. Overall, students who were treated with the logical inference-based English-style debate learning model obtained an average score of 86.1. The results of this study are expected to be able to elaborate scientific thinking problems and become a reference for the application of innovative and fun learning models.